When Is Growth Pro-Poor? : Evidence from the Diverse Experiences of India's States - Ravallion, Martin, 1952- 1952- (The World Bank, 1999)
December 1999 - Nonfarm economic growth in India had very different effects on poverty in different states. Nonfarm growth was least effective at reducing poverty in states where initial conditions were poor in terms of rural development and human resources. Among initial conditions conducive to pro-poor growth, literacy plays a notably positive role. Ravallion and Datt use 20 household surveys for India's 15 major states, spanning 1960-94, to study how initial conditions and the sectoral composition of economic growth interact to influence how much economic growth reduced poverty. The elasticities of measured poverty to farm yields and development spending did not differ significantly across states. But the elasticities of poverty to (urban and rural) nonfarm output varied appreciably, and the differences were quantitatively important to the overall rate of poverty reduction. States with initially lower farm productivity, lower rural living standards relative to those in urban areas, and lower literacy experienced a less pro-poor growth process. This paper - a joint product of Poverty and Human Resources, Development Research Group, and the Poverty Reduction and Economic Management Sector Unit, South Asia Region - is part of a larger effort in the Bank to better understand the conditions required for pro-poor growth. The authors may be contacted at mravallion@worldbank.org or gdatt@worldbank.org